PENGOLAHAN LIMBAH CAIR LABORATORIUM DENGAN ADSORPSI SERTA PRETREATMENT NETRALISASI DAN KOAGULASI - Nurhayati, Indah; Sugito, Sugito; Pertiwi, Ayu (Jurnal Sains & Teknologi Lingkungan, 2018)
The liquid waste of the UNIPA Surabaya Environmental Engineering laboratory has not fulfilled the requirements of the Minister of Environment Regulation Number 5 of 2014, so it needs to be processed so as not to pollute the Environment. This study aims to examine the effect of the coagulant dose of Poly Alum Chloride (PAC) on decreasing Pb, Cr, and TDS, assessing the quality of wastewater after neutralization, coagulation and adsorption especially for Pb, Cr, TDS, and pH parameters. The variables of this study were PAC doses of 150 mg / L, 225 mg / L and 300 mg / L. The research was carried out on a laboratory scale with a continuous system with downflow. The adsorption media used are fibers, coconut fiber, bagasse activated carbon and multilevel zeolites in the reactor from the PVC pipe. Adsorption process is carried out for 2 hours and sampling every 15 minutes. The results of this study showed that the PAC 300 mg / L produced the highest reduction efficiency, namely TDS 13.7% Cr 97%, Pb 93.5%, and the quality of waste after neutralization, coagulated and adsorbed in the 15th minute having TDS 1.810 levels ppm, Cr total 0.36 ppm, Pb 0.66 ppm so that wastewater has met the quality standards in accordance with Regulation of the Minister of Environment No. 5 of 2014 while the pH of 5.42 does not meet the quality standard.